The Inner City as a Residential Area for the “Young Elderly”? - Rabe, A.; Hohn, U. (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Is the inner city an attractive place for the “young elderly” to live? During decades suburbanization was the dominant pattern of city development in Germany. However, since the 2000s an increasing attraction of urban living and the trend of re-urbanization are discussed in research as well as in public. Due to an increasing average age and life expectancy of the population as a main sub-process of demographic change in Germany, the question arises whether the inner city as a residential area also becomes more attractive for the elderly. Especially “young elderly” people (ca. 50–70 years old) are getting into focus. Because of a transitional phase of their lives, they might show a greater willingness to change the residential location to adapt to their new needs.In order to analyze the attractiveness of the inner city as a residential area for the “young elderly”, residential location decisions, which were realized between 2010 and 2012, were investigated using the city of Bonn as an example. The results of a survey and in-depth interviews show that the inner city cannot be considered as a homogeneous space, but that small-scale differences in the attractiveness as a residential area exist. In summary, the “young elderly” prefer the fringe of the inner city while the city center is important for their shopping and leisure activities, but not as attractive for them to live. However, also within the fringe of the inner city more and less attractive residential areas can be identified corresponding to lifestyle and income of the “young elderly”.
Keywords: Residential location decisions; Re-Urbanization; Young elderly; Inner city living; Inner city